PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS PENDEKATAN ACCELERATED LEARNING PADA MATA PELAJARAN BAHASA INDONESIA - Elia Rosa (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
Learning devices are tools or components used in the learning process needed to support the learning process. the purpose of this study is to develop learning tools based on the accelerated learning approach. The implementation of this research was carried out on the third grade students of SDN 003Tasik Juang. This research is a research development. Product trials are carried out in two stages, namely with trial 1 (limited test) and trial 2 (limited deployment). The results of the study showed that, learning tools developed using the accelerated learning approach were declared valid and feasible to be used by obtaining a percentage of 83.5% the category was very valid. Learning tools developed using the accelerated learning approach are declared practical based on the results of the observation sheet of the implementation of the learning process with an average value of 87.5 very good categories as well as from student questionnaire response data with an average value of 88.5 with very good categories. The learning tools developed are effective based on the acquisition of learning outcomes that are above the minimum completeness criteria with classical completeness of 84.9%. Based on these results it can be concluded that the development of learning tools based on a valid, practical, and effective accelerated learning approach was developed in students of class III SDN 003 Tasik Juang